AN INVESTIGATION INTO THE EFFECT OF CARBONATED THIN AND THICKENED LIQUIDS ON THE DURATION OF SWALLOWING IN NORMAL HEALTHY INDIVIDUALS. (2017)
Carbonic acid is believed to heighten sensory input to the nervous system and trigger a faster or more effective swallow. (Logemann 1996, 1998) Previous research into the effect of carbonic acid on measures of pharyngeal transit time, pharyngeal retention of residue, and penetration/aspiration have highlighted its potential as an effective sensory stimulant. Further investigation into how the normal swallowing process responds to oropharyngeal sensory input is required before diet plans that include trigeminal irritants may be used in dysphagia management. Using a swallowing reaction time test, the present study was designed to determine whether carbonation, an acidic chemical stimulus, effectively facilitates positive changes, i.e. reduced total swallow duration (TSD), in the swallowing physiology of 30 healthy subjects with normal oropharyngeal swallow. In addition, the study aimed to determine whether thickened boluses will differentially modify swallowing latencies compared with thin carbonated and non-carbonated liquids. Palatability and subjective difficulty of swallow rating scales were also collected for each stimuli to determine an overall effective and palatable stimulus. The test beverages included; filtered tap water, a condition with no stimulation, fizzy water, a stimulation by carbonic acid alone, Ribena, a gustatory stimulation (sweet taste) without carbonic acid and Coca-Cola, a gustatory stimulation (sweet taste) with carbonic acid. Aims; 1. What is the effect of flavoured and non-flavoured carbonated thin liquids on total swallow duration, when compared to flavoured and non-flavoured; (A) Thin non-carbonated liquids (B) Thickened (stages 1-3) non-carbonated (C) Thickened (stages 1-3) carbonated liquids. 2. How do the palatability and SDS ratings of flavoured and non-flavoured carbonated thin liquids differ from, flavoured and non-flavoured; (A) Thin non-carbonated liquids (B) Thickened (stages 1-3) non-carbonated liquids (C) Thickened (stages 1-3) carbonated liquids. It was hypothesised that varying carbonation, consistency and flavour would affect TSD, palatability and SDS and thus provide new data on how they interact with swallowing physiology. The results showed that thin carbonated (T-C) stimuli did not significantly reduce TSD or palatability in comparison with thin non-carbonated stimuli. T-C stimuli did significantly reduce SDS. Thin stimuli significantly reduced TSD, palatability and SDS in comparison with thickened stimuli. Flavour significantly reduced TSD, palatability and SDS when compared to non-flavoured. Possible explanations for differences between the current findings and those of earlier studies are discussed.